Investigating local climatic factors that affected pineapple production, in Lampung Indonesia - Katarina Manik, Tumiar; Sanjaya, Purba; Pandu Perdana, Onny Chrisna; Arfian, Dudy (International Journal of Environment, Agriculture and Biotechnology, 2019)
In Indonesia, pineapple is one horticulture commodity which has high potential in international fruits trade, therefore the plantation should maintain its high yield and good fruit quality. One cause that determined pineapple yield was water availability even though pineapple could resist dry period. Irrigation is always needed in pineapple plantation, however, this is a costly treatment and high irrigation level has not always lead to significant increases in crop productivity. This study aimed to investigate the possible factors that determined pineapple productions in Indonesia biggest pineapple plantation in Indonesia using all climate factors available. Some statistics methods were used to utilize the available climate data to analyze the rainfall probability, rainfall frequency distribution, evapotranspiration estimation, water balance, water use efficiency and weather impacts on fruit qualities. The results showed that water from average annual rainfall should be adequate for the pineapple water needs, however there were months had water deficit and needed irrigation. Low evapotranspiration rate reflected dry soil which could be the results of high air and soil temperature. This high temperature also affected on fruit qualities. It is suggested to conduct researches on how pineapple productions and qualities that plants under shading trees.